Dynamics of Collaboration in the Activities of Krishi Vigyan Kendras - M.J.Chandre Gowda,; R.K.Samanta, (Journal of Agricultural Extension Management, 2025)
Agricultural extension is a professional communication intervention deployed by organisations / insituations. Regardless of how it i provided, Agricultural Extension has been an essential component of agriculture and rural development process. It is often seen as a linker between technology generation and technology utilisation and hence research-extension linkages are on ly emphasized for its success. While the importance of knowledge input in the success of extension cannot be discounted, the support of other organisations engaged in providing supply and services to the farming community cannot be underestimated